Aktivitas Sediaan Gel Antiseptik Tangan Berbahan Aktif Ekstrak Fraksi Etanol Daun Sungkai (Peronema canencens Jack.) terhadap Beberapa Bakteri Patogen (Journal of Tropical Pharmacy and Chemistry, 2015)
A research which antiseptic hand gel preparations containing the active leaf extract fraction ethanol Sungkai (Peronema canencens Jack.) has been done. This study aims to know is antiseptic activity Sungkai leaf fraction (P. canescens. Jack) in vitro against to several microbial pathogens in the preparation of antiseptic hand gel, and to know determine the best concentration of ethanol fraction Sungkai leaf in the preparation of antiseptic gel hands each strain of pathogenic bacteria. Test materials obtained by fractionation of the ethanol extract of the leaf fraction Sungkai, further formulated into a gel base antiseptic, tested its activity against several bacterial pathogens, and determine the best concentration of ethanol fraction Sungkai leaf in the preparation of antiseptic hand gel against Staphylococcus aureus, Salmonella thyposa, Escherichia coli and Bacillus subtilis bacteria. Antibacterial testing using method in vitro solid diffusion test. The results showed the concentration of ethanol fraction in gel dosage of active antiseptic against Staphylococcus aureus, Salmonella thyposa, Escherichia coli and Bacillus subtilis bacteria. The best concentration of ethanol extract in the preparation of antiseptic gel was 4% effective at inhibiting or kill the to three bacteria.